The Phoenix of Counterinsurgency - Mockaitis, Thomas (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2007)
Abstract For the last three decades of the twentieth century, soldiers and academics confidently proclaimed the death of counterinsurgency (COIN) as a major form of warfare. They asserted that the vast majority of COIN campaigns occurred at the end of the colonial era as nationalist insurgents ushered European powers out of Africa and Asia. The passing of empires meant the end of this most vexing form of warfare, so the reasoning went. The United States, in particular, turned its back on unconventional conflict, embittered by the experience of Vietnam and committed to the defense of Western Europe and South Korea. The end of the Cold War had little impact on this mindset, especially when the first Gulf War seemed to vindicate faith in conventional arms. The complex humanitarian missions of the 1990s bore a striking resemblance to COIN for those who wished to look beneath the surface differences. The Somalia debacle, however, reinforced the conviction that irregular operations should be avoided, not studied. Only the inescapable realities of Afghanistan and Iraq have forced the rediscovery of effective COIN methods and then only after much blood and treasure had been wasted. This article traces the evolution of COIN and argues that it will remain a prevalent form of warfare for the foreseeable future.